(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This interview aims to learn about Quebec’s educational aspects focused on an intercultural perspective on teaching Visual Arts and identify the appreciation approaches adopted by university professor Adriana de Oliveira in her teaching practices. In this way, we sought to understand the importance of interculturality in projects that relate art to social issues; the aesthetic appreciation of contemporary images in the context of basic education; how these aspects are addressed in the training of future Visual Arts teachers; and how they are explored in everyday school life by these professionals. Furthermore, throughout the questions we sought to identify how these elements can be explored by art teachers in the context of basic education.